Clinical and anatomical features of myopia - Jonas, Jost B.; Panda-Jonas, Songhomitra; Dong, Li; Jonas, Rahul A. (Asia-Pacific journal of ophthalmology, 2024)
The purpose of the review is to summarize clinical and anatomically-related aspects of myopia. Recent studies have revealed macular atrophy as myopic maculopathy (MMP) stage-4 was accompanied by a central Bruch´s membrane (BM) defect associated with a subretinal proliferation (as sign of previous macular neovascularization). Patchy atrophies (MMP-stage 3) could be differentiated into those without versus with BM defects/subretinal proliferations. BM defects and subretinal proliferations were associated with each other (OR: 78.3; P<0.001). Fundus tessellation as MMP-stage-1 correlated with visual acuity reduction, suggesting pathological changes already at MMP stage 1, in addition to a leptochoroid as risk factor. Myopic parapapillary beta zone (potentially caused by an axial elongation-related enlargement of the retinal pigment epithelium [RPE] layer opening; characterized by small or no alpha zone, few or no RPE drusen at its border, normal BM thickness) can be differentiated from glaucomatous parapapillary beta zone (characterized by alpha zone, RPE drusen, and thickened BM). The overlying retinal layers extended into the parapapillary zones, deeper than the superficial layers. Prevalence of non-glaucomatous optic neuropathy increased non-linearly with longer axial length in highly myopic eyes and was a major cause for vision loss in high myopia. In patients aged 85+years, prevalence of MMP stage 3 or 4 in highly myopic eyes (axial length ≥ 26.5mm) was about 75%. Myopia was associated with a lower prevalence of diabetic retinopathy, age-related macular degeneration and angle-closure glaucoma, while high myopia, more than moderate myopia, was associated with higher prevalence and incidence of open-angle glaucoma.